Analysis of Changes in Corneal Topography after 27-Gauge Transconjunctival Microincision Vitrectomy Combined with Cataract Surgery. (10th July 2019) - Watanabe, Tomoyuki; Gekka, Tamaki; Watanabe, Akira; Nakano, Tadashi
Abstract : Purpose . To investigate changes in the corneal shape before and after vitrectomy, over a period of time, using a 27-gauge system. Methods . Forty-five eyes underwent a combination of cataract surgery and vitrectomy. The surgeries were performed using a 27-gauge transconjunctival vitrectomy system, in which the corneal topography could be performed up to three months after the surgery. The surgeries were performed for an epiretinal membrane in 11 eyes, a macular hole in 14 eyes, and rhegmatogenous retinal detachment in 20 eyes. All of the surgeries were performed by the same surgeon, and in all cases, a 4-port 27-gauge vitrectomy device was used. Cataract surgery in all patients was performed with a 2.4 mm corneoscleral incision at 11 o'clock. The surgeries were performed without suturing the operative wound in all cases. Corneal topography was performed using a TMS-4 topographer (Tomey Corporation, Tokyo, Japan). The examinations were performed the day before and 1 day, 1 week, 1 month, and 3 months after the surgery. The results of corneal topography for the spherical, regular astigmatic, asymmetric, and high-order irregular astigmatic components were compared before and after surgery. Results . No significant differences were seen in any of the components in the epiretinal membrane group, but significant differences were seen in the asymmetric components and the high-order irregular astigmatic components between the macular hole and rhegmatogenous retinal detachment groups (p < 0.05 ). There were no significant changes in intraocular pressure on any measurement time in the postoperative period compared to preoperative intraocular pressure. Conclusion . Irregular astigmatism was seen after surgery when 27-gauge vitrectomy with a 4-port system was performed together with cataract surgery with a 2.4 mm incision.